A Binaural Steering Beamformer System for Enhancing a Moving Speech Source - Adiloğlu, Kamil (Trends Hear, 2015)
In many daily life communication situations, several sound sources are simultaneously active. While normal-hearing listeners can easily distinguish the target sound source from interfering sound sources—as long as target and interferers are spatially or spectrally separated—and concentrate on the target, hearing-impaired listeners and cochlear implant users have difficulties in making such a distinction. In this article, we propose a binaural approach composed of a spatial filter controlled by a direction-of-arrival estimator to track and enhance a moving target sound. This approach was implemented on a real-time signal processing platform enabling experiments with test subjects in situ. To evaluate the proposed method, a data set of sound signals with a single moving sound source in an anechoic diffuse noise environment was generated using virtual acoustics. The proposed steering method was compared with a fixed (nonsteering) method that enhances sound from the frontal direction in an objective evaluation and subjective experiments using this database. In both cases, the obtained results indicated a significant improvement in speech intelligibility and quality compared with the unprocessed signal. Furthermore, the proposed method outperformed the nonsteering method.